CZECH-SLOVAK COMPARATIVE STUDIES “REBORN”. A NEW ASSOCIATION ON THE WAY - Zelenka, Miloš (Porównania, 2016)
The paper conveys information on the current state of Czech and Slovak comparatist thought as regards its methods, thematical orientation and institutional base. Czech and Slovak comparative research has always been a complementary whole embracing, on the one hand, the tradition of Slavonic studies grounded in structural aesthetics (S. Wollman) and, on the other, the endeavour to develop the theory of interliterarines and interdisciplinary study of the world literature (D. Ďurišin). Much to our regret, the disruption of this “symbiosis” at the turn of 1990s resulted in losing contacts with the rest of the world. Therefore the prime objective of the newly established Czech-Slovak Association of Comparative Literature, based in the Institute for World Literature SAV, Bratislava, is to encourage Czech and Slovak literary research. The constitutive members of this association already in 2013 participated in the 20th World Congress of Comparative Literature in Paris (AILC/ICLA) so as to present the English version of their World Literature Studies journal under the title Comparative Literary Studies as Cultural Criticism. The first joint conference of Czech and Slovak comparatists (Slavica Litteraria 18, 2015, No. 1) was held in Bratislava in February 2015. For our next event, the 21st AILC Congress in Paris 2016, Czech and Slovak scholars, together with their foreign colleagues, have prepared a joint panel presentation Old and New Concepts of Comparative Literature in the Globalized World. Convinced that theoretical and methodological discourse is carried on in various languages and power stands, present-day Czech and Slovak comparative research, while following the pillar traditions of the past, espouses modern inspirations that obviously relinquish historical poetics and the theory of interliterariness, bound for exploring new cultural identities, post-colonial and area studies.